The human vulnerability as an important social element for combating human trafficking and victims (Revista do Tribunal Regional Federal da 3ª Região, 2019)
Going back to the reasons why the first international treaty to combat human trafficking was aimed only at white women, this work points to the recurring difficulties of humanity itself in granting broad and unrestricted legal protection to any and all trafficked human beings, especially when they are vulnerable. Even so, when we reach this global legal text, we turn our gaze to Brazil's legal history, which, even after the late adoption of the classification of all types of human trafficking in 2016, has failed to combine the verb to abuse with the condition (not uncommon among us) of the victim's vulnerability, as well as to state the total invalidity of their eventual consent. Although these apparent absences can be overcome by criminal law, we question whether they could be symptoms of a society that, through its most varied actors, public officials or not, does not identify and, if it does, does not respect the vulnerability of others, which, as a basic concept, goes beyond individual conditions, including social and institutional conditions. We point to documentation that indicates the influence of these prejudices or discriminations, which then prejudge the victim and favor the actions of the vilest of criminals, the human trafficker. We conclude that, if a society cannot be changed so quickly, it must be informed, and public officials must be trained to pay attention to the specificities of this crime and committed to listening to and welcoming victims in a humanized way.
Keywords: human trafficking; human vulnerability; prejudice; social discrimination